Development of a UPLC-MS/MS method for quantifying KPT-335 (Verdinexor) in feline plasma for a study of PK - Yang, Yuxin; Qiu, Jicheng; Kong, Jingyuan; Cao, Yuying; Liu, Yu; Chen, Sumeng; Wen, Zeyu; Sun, Feifei; Cao, Xingyuan (Frontiers in Veterinary Science, 2024)
KPT-335 (Verdinexor) is a novel SINE that potently inhibits the nucleoprotein Exportin 1 (XPO1/CRM1) of tumor cell lines and reduces the replication level of the influenza virus. KPT-335 is mainly used for the treatment of canine tumors. Drugs for the effective treatment of feline tumors are currently unavailable in China. KPT-335 may have potential in the treatment of cat tumors. However, the effects of KPT-335 in cats are unreported, and no relevant methodology has been established for pharmacokinetic studies. In this study, a UPLC-MS/MS method was developed to determine KPT-335 concentrations in cat plasma, followed by pharmacokinetic studies. Briefly, plasma proteins are precipitated with acetonitrile, and the supernatant was collected for detection after centrifugation. The linearity for KPT-335 in cat plasma was in the range of 5–1000 ng/mL. Satisfactory accuracy and precision were obtained. The intra-day accuracy was between −4.1% and 10.48%, the precision was less than or equal to 4.65%; the inter-day accuracy was between −0.11% and 8.09%, and the precision was less than or equal to 5.85. Intra-day and inter-day accuracy and precision were within regulatory limits. The results of preliminary pharmacokinetic studies were as follows: Tmax was 1.46±0.51 h; Cmax was 239.54±190.60 ng·mL-1; T1/2 was 5.16±2.30 h; AUC0-t was 1439.85±964.64 ng·mL-1·h. The AUC0-∞ was 1589.82±1003.75 ng·mL-1·h. The purpose of this study was to develop a rapid and simple UPLC-MS/MS method to detect KPT-335 concentration in cat plasma and to conduct preliminary pharmacokinetic studies to support the future application of KPT-335 in felines.